Dietary supplementation of Spirulina platensis and Saccharomyces cerevisiae on egg quality, physiological condition and ammonia emission of hens at the late laying period - H. I. Wahyuni; T. Yudiarti; E. Widiastuti; T. A. Sartono; I. Agusetyaningsih; S. Sugiharto (Diponegoro University, 2023)
The study was aimed to evaluate the effect of Spirulina platensis and Saccharomyces cerevisiae or its combination on egg quality, physiological condition and ammonia excretion of hens at the late lay-ing period. At 81 weeks old, 144 Lohmann Brown layer chickens were divided into four treatment groups included CON (hens fed basal feed), SP (basal feed + 0.3% S. platensis), SC (basal feed + 0.2% S. cerevisiae), and SPSC (basal feed + 0.3% S. platensis + 0.2% S. cerevisiae). At the end of the study, eggs, intestinal mucosa, digesta, excreta and blood sample were collected. Results showed that albumin index was higher (P<0.05) in SPSC group than in CON, SP and SC. The yolk index and yolk colour were greater (P<0.05) in SP and SPSC groups than in CON and SC. The erythrocyte values were high-er (P<0.05) in SP group compared to CON, SC and SPSC groups. The ileum pH was higher (P<0.05) in SP than in CON, SC and SPSC. Lactic acid bacteria counts were lower (P<0.05) in the caecum of SC and SPSC than in CON and SP groups. The lower (P<0.05) counts of lactose-negative Enterobacte-riaceae were shown in SC and SPSC than in CON. The excreta pH was lower (P<0.05) in SC group compared to CON, SP and SPSC groups. There were better (P<0.05) protein digestibility coefficient and nitrogen retention in SPSC group than others. Faecal ammonia decreased (P<0.05) in SP, SC and SPSC groups. In conclusion, S. platensis improved egg yolk index and colour, increased erythrocyte counts and played an important role in maintaining the balance of bacteria in the intestine resulting in reduced ammonia excretion. Dietary inclusion of S. cerevisiae reduced ammonia excretion of laying hens during the late laying period.